Analisis Contagius Effect Menggunakan Garch Model: Bukti dari Asia Tenggara - Tuti Zakiyah; Arya Samudra Mahardhika (Universitas Batanghari, 2023)
This study aims to investigate the impact of the dynamic relationship dynamics during the Covid-19 pandemic between gold prices, oil prices and stock returns in Asean-5 countries related to the contatagion effect theory with evidence using GARCH Models analysis. The types of samples in this study are saturated samples, namely Gold prices, Oil prices, Composite Stock Price Index (Indonesia) JCI, Kuala Lumpur Composite Index/KLCI (Malaysia), Straits Times Singapore (STI), Securities Exchange of Thailand Index/SETI (Thailand). ), and the Philippine Stock Exchange/PSE (Philippines), during the Covid-19 pandemic, from March 11, 2020 to October 30, 2021, totaling 430 samples. The analytical technique used in applying the GARCH model in this study uses the Eviews 10 software program, with the results for the gold dependent variable the results state that the Indonesian Composite Stock Index (IHSG), Kuala Lumpur Composite Index (KLCI), STI (Singapore), Securities Exchange Thailand Index/SETI (Thailand), and Philippine Stock Exchange/PSE (Philippines), have a consistent relationship with the price of Gold, the contingent theory of effects is proven to occur in 5 countries in the sample. As for the dependent variable oil, the results state that the price of the oil price variable is only the theory of contingent effects, which has been proven to occur in 4 countries and has not been proven to occur in the Kuala Lumpur Composite Index (KLCI) Malaysia.